Projection pricing for musyarakah mutanaqisah home financing with the use of rental yield as the reference benchmark pricing - Redzuan, Nur Harena; Kassim, Salina (Science Publishing Corporation, 2018)
The Islamic financial institution offers home financing products that are fully compliant with the Shariah. However, these Islamic financial products are in the absence of a reference benchmark pricing which is free from the interest rate. There is a call for introducing a reference benchmark pricing an alternative to interest-based borrowing and free from any of riba element. Usmani (2008) stressed that even though using an interest-based benchmark pricing is allowed and the practice is highly discouraged. He further argued that the practice of reference benchmarking pricing against interest rate does not advance the basic philosophy of promoting Islamic economy, whereby it makes no impact on the distribution system. The main objective of this study is to assess the projection of the pricing for musyarakah mutanaqisah home financing. The projection pricing is performed with the viability of adopting the rental yield as a reference benchmark pricing, which is the alternative to relying on the market interest rate. The forecasting technique of the Artificial Neural Network (ANN) model is adopted to assess the predictability of the rental yield of the housing market for a period of 20 years. Subsequently, the forecast data is used to project the pricing of musharakah mutanaqisah home financing product using the simulation method. The projection pricing of musharakah mutanaqisah is compared with the bai bithaman ajil (debt-based financing) and the conventional home financing. Based on simulation exercise, there is a significance difference between total payment by the customer for these two products. The Islamic financial institution can consider relying on the rental yield as the reference benchmark pricing to price the home financing product.